(26+2x)(10+2x)=720

Simple and best practice solution for (26+2x)(10+2x)=720 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (26+2x)(10+2x)=720 equation:


Simplifying
(26 + 2x)(10 + 2x) = 720

Multiply (26 + 2x) * (10 + 2x)
(26(10 + 2x) + 2x * (10 + 2x)) = 720
((10 * 26 + 2x * 26) + 2x * (10 + 2x)) = 720
((260 + 52x) + 2x * (10 + 2x)) = 720
(260 + 52x + (10 * 2x + 2x * 2x)) = 720
(260 + 52x + (20x + 4x2)) = 720

Combine like terms: 52x + 20x = 72x
(260 + 72x + 4x2) = 720

Solving
260 + 72x + 4x2 = 720

Solving for variable 'x'.

Reorder the terms:
260 + -720 + 72x + 4x2 = 720 + -720

Combine like terms: 260 + -720 = -460
-460 + 72x + 4x2 = 720 + -720

Combine like terms: 720 + -720 = 0
-460 + 72x + 4x2 = 0

Factor out the Greatest Common Factor (GCF), '4'.
4(-115 + 18x + x2) = 0

Factor a trinomial.
4((-23 + -1x)(5 + -1x)) = 0

Ignore the factor 4.

Subproblem 1

Set the factor '(-23 + -1x)' equal to zero and attempt to solve: Simplifying -23 + -1x = 0 Solving -23 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '23' to each side of the equation. -23 + 23 + -1x = 0 + 23 Combine like terms: -23 + 23 = 0 0 + -1x = 0 + 23 -1x = 0 + 23 Combine like terms: 0 + 23 = 23 -1x = 23 Divide each side by '-1'. x = -23 Simplifying x = -23

Subproblem 2

Set the factor '(5 + -1x)' equal to zero and attempt to solve: Simplifying 5 + -1x = 0 Solving 5 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -1x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -1x = 0 + -5 -1x = 0 + -5 Combine like terms: 0 + -5 = -5 -1x = -5 Divide each side by '-1'. x = 5 Simplifying x = 5

Solution

x = {-23, 5}

See similar equations:

| 6(x+1)=3(2x+8)-18 | | 67857+8375783= | | -(7y+1)-(-6y-8)=5 | | y=2.70+.20(27) | | -x=-3x+4 | | 7.70=2.70+.20x | | 3x^2+3x-32=0 | | (26+2x)(10+2x)=0 | | x^2+41=10x | | 8p+3=3p-37 | | Chasity+Jason= | | 7(7y-8)=21y | | 4x^2=36x-81 | | x(5x+5)=2x^2-2X+20 | | 3(x-6)=3 | | (x+6)(4x+3)=-17 | | (x+4)(4x+1)=-11 | | 3z=54 | | x(15x+32)=60 | | 4(0)+9y=8 | | 4(0)+9(7)=8 | | 16a^2+8a-35= | | X^13=17 | | 4(x+5)-10= | | X^5=13 | | 3x^2=8-10x | | .6667x-5+1.8333x-2=13 | | x^2=22x-121 | | 25x^2=90x-81 | | .007x-1.3=.05x-1.1 | | 23x^2-8x=0 | | 25x^2=70x-49 |

Equations solver categories